Differences in clinical characteristics of cervical spine injuries in older adults by external causes: a multicenter study of 1512 cases - Noriaki Yokogawa; Satoshi Kato; Takeshi Sasagawa; Hiroyuki Hayashi; Hiroyuki Tsuchiya; Kei Ando; Hiroaki Nakashima; Naoki Segi; Toru Funayama; Fumihiko Eto; Akihiro Yamaji; Satoshi Nori; et al. (Scientific Reports, 2022)
Abstract Although traumatic cervical spine injuries in older adults are commonly caused by minor traumas, such as ground-level falls, their prognosis is often unfavorable. Studies examining the clinical characteristics of cervical spine injuries in older adults according to the external cause of injury are lacking. This study included 1512 patients of ≥ 65 years of age with traumatic cervical spine injuries registered in a Japanese nationwide multicenter database. The relationship between the external causes and clinical characteristics, as well as factors causing unfavorable outcomes at the ground-level falls, were retrospectively reviewed and examined. When fall-induced cervical spine injuries were categorized and compared based on fall height, the patients’ backgrounds and injury statuses differed significantly. Of note, patients injured from ground-level falls tended to have poorer pre-injury health conditions, such as medical comorbidities and frailty, compared with those who fell from higher heights. For ground-level falls, the mortality, walking independence, and home-discharge rates at 6 months post-injury were 9%, 67%, and 80%, respectively, with preexisting medical comorbidities and frailty associated with unfavorable outcomes, independent of age or severity of neurological impairment at the time of injury.